Animal welfare at German abattoirs: insights into the occurrence of violations against laws and regulations from official veterinarians and judicial decisions - Schneidewind, Stephanie Janet; Langforth, Susann; Meemken, Diana (Frontiers in Veterinary Science, 2024)
The article titled "Animal Welfare at German Abattoirs: Insights into the Occurrence of Violations against Laws and Regulations from Official Veterinarians and Judicial Decisions" aligns with the scope of the selected journal, as it seeks to contribute to advancements in animal welfare by identifying potential risks to well-being. This research provides valuable insights into the occurrence of various animal welfare violations at German abattoirs, laying the foundation for enhancing the education and training of official veterinarians and abattoir employees. Seeing as this paper relates to farm animal welfare in terms of public policies and associated consequences at the abattoir, the section "Frontiers in Animal Science -Animal Welfare and Policy" could be a good fit.